ANALISIS HUKUM TERHADAP PENDISTRIBUSIAN ZAKAT OLEH BAZNAS KOTA PALU DALAM UPAYA PENGENTASAN KEMISKINAN - Suhri Hanafi; Diana Mukti Wijiastuti; Muhammad Syarif Nurdin (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2023)
Abstract The phenomena of natural disasters such as tsunamis, liquefaction, earthquakes, and also Covid 19 have contributed to increasing poverty in Palu City. This phenomenon is in contrast to the function of the National Amil Zakat Agency (BAZNAS) as an institution or agency tasked with distributing zakat funds as an alternative to poverty alleviation. This study aims to analyze the distribution of zakat by BAZNAS Palu City to alleviate poverty from a legal perspective. The research method used is qualitative research. Based on the results of the research, the zakat distribution mechanism by BAZNAS Palu City is channeled through consumptive and productive assistance. The inhibiting factor for the distribution of zakat funds is influenced by the not-yet-optimal development of amil towards mustahik. From a legal perspective, the distribution of zakat funds by the Amil Zakat Agency (BAZNAS) in Palu City complies with the provisions of Law Number 23 of 2011.   Keywords: BAZNAS, Zakat Distribution, Law.